Garment embedded sweat-activated batteries in wearable electronics for continuous sweat monitoring - Huang, Xingcan; Liu, Yiming; Zhou, Jingkun; Nejad, Sina Khazaee; Wong, Tsz Hung; Huang, Ya; Li, Hu; Yiu, Chun Ki; Park, Wooyoung; Li, Jian; Su, Jingyou; Zhao, Ling; et al. (Npj flexible electronics, 2022)
Thin, soft, and skin-integrated electronic system has great advantages for realizing continuous human healthcare monitoring. Here, we report an ultra-thin, flexible, and garment-based microelectronics powered by sweat-activated batteries (SABs) and applications of powering biosensors and microelectronic systems for real time sweat monitoring. The SAB cell is ultra-thin (1.25 mm) with excellent biocompatibility. The SAB has good electricity output with high capacity (14.33 mAh) and maximum power density (3.17 mW cm −2 ) after being activated by the sweat volume of 0.045 mL cm −2 , which could continuously power 120 light emitting diodes over 3 h. The outputs could maintain stable after repeatable bending. Wireless microelectronics system could be continuously powered by the SABs for 3 h to monitor sweat and physiological information, including sweat Na + concentration, pH, and skin impedance. The reported integrated system provides a potential for solving the power issues of flexible wearable electronics and realizing personalized medicine.